Osteoarthritis, magnetic resonance imaging, and biochemical markers: a one year prospective study. Issue 8 (5th January 2006) - Bruyere, O; Collette, J; Kothari, M; Zaim, S; White, D; Genant, H; Peterfy, C; Burlet, N; Ethgen, D; Montague, T; Dabrowski, C; Reginster, J-Y
Abstract : Objective: To investigate the relation between biochemical markers of bone, cartilage, and synovial remodelling and the structural progression of knee osteoarthritis. Methods: 62 patients of both sexes with knee osteoarthritis were followed prospectively for one year. From magnetic resonance imaging (MRI), done at baseline and after one year, the volume and thickness of cartilage of the femur, the medial tibia, and the lateral tibia were assessed. A whole organ magnetic resonance imaging score (WORMS) of the knee was calculated for each patient at baseline and at the one year visits. This score consists in a validated, semiquantitative scoring system for whole organ assessment of the knee in osteoarthritis using MRI. Biochemical markers (serum hyaluronic acid, osteocalcin, cartilage glycoprotein 39 (YKL-40), cartilage oligomeric matrix protein (COMP), and C-telopeptide of type I collagen (CTX-I), and urine C-telopeptide of type II collagen (CTX-II)) were measured at baseline and after three months. Results: Baseline markers were not correlated with one year changes observed in cartilage volume and thickness. However, an increase in CTX-II after three months was significantly correlated with a one year decrease in mean thickness of medial tibial and lateral tibial cartilage. Patients in the highest quartile of three month changes in CTX-II experienced a mean loss of 0.07 (0.08) mm of their medial thickness, compared with a mean increase of 0.05 (0.19) mm for patients in the lowest quartile (p = 0.04) Multiple regression analysis showed that high baseline levels of hyaluronic acid are predictive of a worsening in WORMS (p = 0.004). Conclusions: These results suggest that a single measurement of serum hyaluronic acid or short term changes in urine CTX-II could identify patients at greatest risk of progression of osteoarthritis.